Antiplatelet and Antithrombotic Activity of a Traditional Medicine, Hwangryunhaedok-Tang - Kim, Kyungho; Do, Hyun Ju; Oh, Tae Woo; Kim, Kwang-Youn; Kim, Tae Hoon; Ma, Jin Yel; Park, Kwang-Il (Frontiers in Pharmacology, 2019)
Platelet activation and accumulation at the site of vascular injury are central to thrombus formation resulted in thrombotic disorders. Medicinal herbs could be one of the most important pharmaceutical agents that ameliorate thrombotic disorders, such as unstable angina, myocardial infarction, stroke, and peripheral vascular diseases. Hwangryunhaedok-tang (HRT) is a traditional herbal medicine that displays multiple biological properties including anti-inflammatory abilities. However, its role in platelet activation has not been fully studied. Hence, we examined whether HRT has a potent inhibitory effect on platelet aggregation and thrombus formation. We demonstrated that HRT (30, 50, and 100 μg/ml) significantly impaired thrombin- and collagen related peptide-induced platelet aggregation, granule secretion, thromboxane B2 generation, and intracellular Ca2+ mobilization. Biochemical studies revealed that HRT is involved in inhibiting the phosphorylation of phospholipase C and protein kinase B. The oral administration of HRT (30, 50, and 100 mg/kg once daily for 1 day and/or 7 days) efficiently ameliorates ferric chloride induced arterial thrombus formation in vivo. Tail bleeding time was not significantly increased. The qualitative phytochemical constituents of the HRT extract were investigated using high-performance liquid chromatography. Our results demonstrated that HRT shows potential antiplatelet and antithrombotic effects without affecting hemostasis. Hence, HRT could be an effective therapeutic agent for the treatment of thrombotic diseases.